MODEL EPIDEMI SEIV PENYEBARAN PENYAKIT POLIO PADA POPULASI TAK KONSTAN - Umam, Yanuar Chaerul; Kharis, Muhammad; Supriyono, Supriyono (Unnes Journal of Mathematics, 2016)
Polio (Poliomyelitis) is a highly contagious disease caused by the polio virus from the genus Enterovirus and family Picorna Viridae. Polio considered dangerous because it can lead to complications, brain damage that causes paralysis of the internal organs, paralysis in the legs, muscles and even death. In this paper,it will be studied mathematical models for the spread of polio that does not cause the death. The mathematical model that is used in this paper is SEIV epidemis models with the recruitmen - death. The analysis includes the determination of the equilibrium point and the associated stability analysis of the equilibrium point. Simulation models are given as a form of approach are the values of the parameters are given as a check on the results of analyzes performed. Vaccination is done can affect the spread of measles in the population